Prospects for Judicial Review of Transnational Private Regulation: Singapore and Canada - Victor V. Ramraj (Tilburg Law Review, 2016)
Transnational regulatory power is increasingly exercised by bodies with no formal accountability to states, although such bodies affect the way individuals, organizations, and states themselves conduct their affairs. As a general rule, courts have been reluctant to engage with these transnational private regulators. This article argues that courts in Singapore and Canada are gradually, if haltingly, fashioning public law principles that enable them to judicially review decisions of domestic private regulators. These principles tend to focus not on the formal status of the body exercising power but on the nature of that power, essentially articulating a functional test. The article argues further that, as it has developed in Singapore and Canada, administrative law contains within it legal tools and principles that would enable courts to judicially review the decisions of transnational private regulators and allow them to play an important role in shaping the emerging norms that govern transnational regulation.